Eco-city or “steady city” as the way of improvement of living conditions for urban population - Vasilyeva Elena (MATEC Web of Conferences, 2018)
The article is devoted to the creation and development of eco-cities, also known as "steady cities". Experience of creation of the eco-cities in the countries of the world is analyzed during the research. Classification of the eco-cities is offered. The basic principles of eco-cities functioning are considered; Special attention is paid to the formation of the closed production cycle with the maximum return to technological processes and the use of energy saving technologies. According to the author, creation and development of such settlements will make a great contribution to the solution of environmental problems of modern Europe. Improvement of the environment, quality of living conditions of humans, improvement of the population health and providing a healthy lifestyle are possible within the eco-cities. The author believes, that creation of eco-cities is possible in Russia (some examples of the first projects are given). But the author emphasizes, that in our country this tendency is just being started and besides it has no legislative regulation and state support.